Healthcare providers' perceptions on post abortion intrauterine contraception: A qualitative study in central Uganda. - Herbert Kayiga; Emelie Looft-Trägårdh; Amanda Cleeve; Othman Kakaire; Nazarius Mbona Tumwesigye; Josaphat Byamugisha; Kristina Gemzell-Danielsson (PLoS ONE, 2024)
Background Despite access to post abortion intrauterine contraception, the uptake of Intrauterine devices (IUDs) in Uganda remains low. Whether the perceptions of healthcare providers towards IUDs have a role in the provision of post abortion IUDs remains unclear. We explored perceptions on post abortion IUD provision among healthcare providers in Uganda, focusing on barriers and facilitators in regards to provision and uptake. Methods Between 1st August 2022 and 30th September 2022, forty-five in-depth interviews were conducted among healthcare providers of different cadres at sixteen public health facilities in central Uganda. We used the case study design to explore the healthcare providers' perceptions. The interviews were primarily to help us understand the perceptions of healthcare providers towards IUDs. All interviews were audio-recorded and transcribed verbatim. Themes were identified using the conventional inductive content analysis. Results From the analysis, three themes emerged. Theme one covered health system related barriers in regards to IUD provision such as healthcare providers' and health facility challenges. The second theme focused on the challenges in post abortion contraceptive counselling focusing on IUDs. The third theme covered the motivating factors and participants' views on how to scale up IUD uptake and provision within post abortion care in Uganda. We found that lack of appropriate knowledge and skills on IUD provision, and heavy workloads, negatively impacted IUD provision. Inadequate facilities, IUD stock-outs, and minimal community sensitization also limited the utilization of IUDs. Furthermore, language barriers, community misconceptions around IUDs, long travel distances to the health facility, and partner refusal, contributed to the low uptake of post abortion IUDs. To address the identified barriers and scale up post abortion IUD provision, participants recommended addressing health system barriers, regular in-service refresher trainings, mentoring and supervision. They emphasized the importance of addressing contraceptive misconceptions and men's opposition to IUDs through community sensitization. Conclusion In this study we identified several barriers to post abortion IUD provision, highlighting an urgent need to address health system barriers including healthcare providers' skills and knowledge gaps, supply chain challenges, and to ensure that facilities are conducive to quality contraceptive counselling. Provision of on-job refresher trainings, mentoring and supervision, are key motivators that can be utilized in supporting healthcare providers towards post abortion IUD provision. To further increase uptake, efforts are needed to dispel contraceptive myths and misconceptions at the community level.